Decolorization of the aqueous Safranin O dye solution using Thuja orientalis as biosorbent. - Edan Al- Mammar, Dunya (Iraqi Journal of Science, 2023)
The object of this study was to evaluate the efficiency of safranin O (SFO), dye removal with application of Thuja orientalis as a low-cost biosorbent. The biosorption equilibrium level was determined as a function of pH, adsorbent dose, contact time and temperature. Surface area and pore size distribution were measured for the adsorbent. Thuja has a good removal effeciency for SFO dye. The adsorption kinetics data were best fit for the pseudo-second order kinetic (the regression coefficient = 0.999). The experimental equilibrium adsorption data are tested for the Langmuir, freundlich,Temkin and Dubinin-Radushkevich isotherm modles. From the values of the regression coefficient the results indicate the following order to fit the isotherm Freundlich > Temkin > Dubinin-Radushkevich > Langmuir. A chemical adsorption process was indicated by the value of the mean free energy of adsorption obtained from the Dubinin-Radushkevich isotherm. Standard free energy of adsorption (ΔG°) and the change in the standard enthalpy (ΔH°) and the standard entropy (ΔS°) were calculated to predict the nature of adsorption.